RELIGION AND NATIONAL INTEGRATION - Rose, John (Journal of Dharma, 2000)
India is a multi-religious, multi-cultural and multi-lingual nation. Although she is defined in terms of "unity in diversity", it is not an easy task to hold her together as a united Bharat. National integration or unity comes as a great challenge to all citizens to discover the authentic religious spirit inherent in every human heart, the root of nationalism and patriotism.